Cooperative granaries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Granaries By M Hoogland & P Holen, co-publication Agromisa CTA, Agrodok No. 25. 2000. 82 pp. ISBN 90 72746 95 3 CTA number 1009. 5 credit points